Making Spatial Change in Pakistan Cities Growth Enhancing - Yuen, Belinda; Choi, Songsu (World Bank, Washington, DC, 2014)
Cities' development matters to Pakistan. It is central to economic growth, job creation and quality of life. This is also one of the core themes in the 2011 Government of Pakistan Framework for Economic Growth (FEG). This paper explores the conditions for growth-enhancing spatial change in Pakistan s cities. Cities' development matters to Pakistan. Two strands of analysis are developed. First, it reviews the performance and impact of land use planning in Pakistan's cities while understanding the institutional culture and rules of the game of urban development practices. Given limited availability of urban data, much of this analysis is based on Pakistan's most urbanized province: Punjab, and large cities, primarily Lahore and Karachi. Second, it uses meta-analysis to suggest an agenda of policy options and priorities that could strengthen Pakistan's prudent implementation of spatial potentials and help materialize its cities' creative capital.Following the introduction the paper examines the critical role cities have in Pakistan's economy and development performance. It provides an analysis of Pakistan's current approach to urban development, examining Pakistan's urban planning and development institutions, legislation and practices with the view to identify critical consequences and constraints hampering balanced urban development. Consequently it offers an agenda of objectives and policy options based on international best practices and key actions to address those constraints and guide spatial change in Pakistan's cities. Lastly, it concludes that successful urban transformation requires political will, a sense of urgency and a commitment for shared action.